Governance by international public administrations bureaucratic influence and global public policies - Cristoph Knill; Bauer, Michael W. (Journal of European public policy series, 2017)
As the demand and necessity for greater international and transnational cooperation increase, the bureaucratic bodies of international organizations are receiving ever more scholarly attention. However, the relevance of International Public Administrations (IPAs) for global policy-making remains neither empirically nor theoretically well understood, and yet little systematic knowledge is available about the influence international bureaucracies may have on policy-making. What makes international bureaucracies influential? Are the sources of their influence on policy-making comparable to that of national public administrations? Is there a need to reflect on other factors than known from the analysis of national bureaucracies or for re-assessing the impact of traditional factors of influence in multilevel constellations? Is there a systematic link between intra-organizational structures and the behavior of the personnel of international bureaucracies and the policy output of their organizations? What are the effects of international bureaucracies' role for particular policies or policy constellations? The different contributions in this volume address these questions from different conceptual perspectives and focus on different tools of administrative governance.